Ultralow‐Power Atomic‐Scale Tin Transistor with Gate Potential in Millivolt. (1st July 2022) - Xie, Fangqing; Ducry, Fabian; Luisier, Mathieu; Leuthold, Juerg; Schimmel, Thomas
Abstract: After decades of continuous scaling, further advancement of complementary metal‐oxide‐semiconductor (CMOS) technology across the entire spectrum of computing applications is today limited by power dissipation, which scales with the square of the supply voltage. Here, an atomic‐scale tin transistor is demonstrated to perform conductive switching between bistable configurations with on/off potentials ≤ 2.5 mV in magnitude. In addition to the low operation voltage, the channel length of the transistor is determined experimentally and with density‐functional theory to be ≤ 1 nm because the atoms instead of electrons are information carriers in this device. The conductance at on‐states of the bistable configurations varies between 1.2 G 0 to 197 G 0 ( G 0 = 2e 2 h −1, e  stands for the electron charge and h for Planck's constant). Thus, the device can supply driving current from 1 to ≈ 375 µA in magnitude for logic circuits with the drain‐source dc voltage at decades of millivolts. The switching frequency of the atomic‐scale tin transistor has reached 2047 Hz. Furthermore, the on/off potentials in millivolts can reduce the energy consumption in the interconnects of integrated circuits at least by ≈ 400 times. Therefore, the atomic‐scale tin transistor has prospects in digital circuits with ultralow‐power dissipation and can contribute to the sustainability of modern society. Abstract : An atomic‐scale tin transistor can perform quantum conductance switching with gate potentials ≤2.5 mV in magnitude. In addition, the channel length of the transistor is determined to be ≤1 nm because atoms are information carriers in this device. Furthermore, the gate potential bypasses the minimum operating voltage ( k B T ln2/ e  = 17.9 mV) of a semiconductor transistor by Landauer's limit.